Reliability of rubrics in the assessment of clinical oral presentation: A prospective controlled study - Muhamood Moothedath (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Rubrics are assessment tools customarily designed to judge a student's skills in diagnosis, clinical assessment, presentations. as well as academic performance. The aim of the present study was to assess the reliability of rubrics in clinical oral presentations by students. MATERIALS AND METHODS: This was a prospective control study that enrolled 300 undergraduate students, students in their internships, and post-graduate students in various clinical streams. Ethical committee approval was obtained before finalizing the study from appropriate regulatory and institutional bodies. A pre-validated questionnaire was designed and distributed to all the participating students. All students were assessed using the traditional examination method as well as by rubric assessment. The responses obtained were compared and statistically analyzed using one-way ANOVA and the Chi-square statistical tool. RESULTS: Rubric assessment was found to have high statistical significance (P < 0.0001) when compared with the traditional method of examination. CONCLUSION: In the present study, rubrics were found to serve as an effective method for judging student skills following a clinical oral presentation. However, due to contradictory scientific evidence, there is a requirement for a large sample size to be included for rubric or traditional assessment method studies.